Exploring the ripple effects of an Australian hospital redevelopment: a protocol for a longitudinal, mixed-methods study - Jeffrey Braithwaite; Kate Churruca; Louise A Ellis; Chiara Pomare; Janet C Long; Brett Gardiner (BMJ Open)
Introduction Hospital redevelopment projects typically intend to improve hospital functioning and modernise the delivery of care. There is research support for the proposition that redevelopment along evidence-based design principles can lead to improved quality and safety. However, it is not clear how redevelopment influences the wider context of the hospital and its functioning. That is, beyond a limited examination of intended outcomes (eg, improved patient satisfaction), are there additional consequences (positive, negative or unintended) occurring within the hospital after the physical environment is changed? Is new always better? The primary purpose of this study is to explore the ripple effects of how hospital redevelopment may influence the organisation, staff and patients in both intended and unintended ways.Methods and analysis We propose to conduct a longitudinal, mixed-methods, case study of a large metropolitan hospital in Australia. The study design consists of a series of measurements over time that are interrupted by the natural intervention of a hospital redevelopment. How hospital redevelopment influences the wider context of the hospital will be assessed in six domains: expectations and reflections of hospital redevelopment, organisational culture, staff interactions, staff well-being, efficiency of care delivery and patient experience. Methods of data collection include a hospital-wide staff survey, semistructured interviews, a network survey, a patient experience survey, analysis of routinely collected hospital data and observations. In addition to a hospital-level analysis, a total of four wards will be examined in-depth, with two acting as controls. Data will be analysed using thematic, statistical and network analyses, respectively, for the qualitative, quantitative and relational data.Ethics and dissemination The study has been reviewed and approved by the relevant Ethics Committee in New South Wales, Australia. The results will be actively disseminated through peer-reviewed journals, conference presentations and in report format to the stakeholders.